Características pre-destete de bovinos simmental (Bos Taurus) y sus cruces con brahman (Bos indicus) en el trópico mexicano - Martínez González, Juan C.; Azuara Martínez, Adalberto; Hernández Meléndez, Javier; Parra Bracamonte, Gaspar M.; Castillo Rodríguez, Sonia P. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The objective of this study was to determine the productive performance in body weight change from birth to weaning, of calves simmental and their crosses with brahman in a beef cattle in the south of Tamaulipas, Mexico. Data were analyzed from 1994 to 2005 years (birth weight BW, n = 947; weaning weight adjusted to 205 days WW205, n = 802; and pre-weaning daily gain weight DGW, n = 802) using the method of minimum square to determine the effects of breed group (BG), year (YC), and season (SC) calving, parity number of cow (PC), and sex of calves (SX); and the interaction of first order on the variables of BW, DGW and WW205. In DGW and WW205 were considered the covariable of BW. The averages for BW, DGW and WW205 were 35.2 ± 6.7, 0.774 ± 0.175 and 194.3 ± 37.3 kg, respectively. The BG was affected (p < 0.01) the DGW and WW205. The YC and SC were important variation sources (p < 0.01) in BW, DGW and WW205. The SC affected (p < 0.05) DGW and WW205. The SX did not have an effect (p > 0.05) on anyone’s variables.